Accuracy of Dose-Saving Artificial-Intelligence-Based 3D Angiography (3DA) for Grading of Intracranial Artery Stenoses: Preliminary Findings - Lang, Stefan; Hölter, Philip; Schmidt, Manuel; Mrochen, Anne; Kuramatsu, Joji; Kaethner, Christian; Roser, Philipp; Kowarschik, Markus; Dörfler, Arnd (Diagnostics, 2023)
Background and purpose: Based on artificial intelligence (AI), 3D angiography (3DA) is a novel postprocessing algorithm for “DSA-like” 3D imaging of cerebral vasculature. Because 3DA requires neither mask runs nor digital subtraction as the current standard 3D-DSA does, it has the potential to cut the patient dose by 50%. The object was to evaluate 3DA’s diagnostic value for visualization of intracranial artery stenoses (IAS) compared to 3D-DSA. Materials and methods: 3D-DSA datasets of IAS (nIAS = 10) were postprocessed using conventional and prototype software (Siemens Healthineers AG, Erlangen, Germany). Matching reconstructions were assessed by two experienced neuroradiologists in consensus reading, considering image quality (IQ), vessel diameters (VD1/2), vessel-geometry index (VGI = VD1/VD2), and specific qualitative/quantitative parameters of IAS (e.g., location, visual IAS grading [low-/medium-/high-grade] and intra-/poststenotic diameters [dintra-/poststenotic in mm]). Using the NASCET criteria, the percentual degree of luminal restriction was calculated. Results: In total, 20 angiographic 3D volumes (n3DA = 10; n3D-DSA = 10) were successfully reconstructed with equivalent IQ. Assessment of the vessel geometry in 3DA datasets did not differ significantly from 3D-DSA (VD1: r = 0.994, p = 0.0001; VD2:r = 0.994, p = 0.0001; VGI: r = 0.899, p = 0.0001). Qualitative analysis of IAS location (3DA/3D-DSA:nICA/C4 = 1, nICA/C7 = 1, nMCA/M1 = 4, nVA/V4 = 2, nBA = 2) and the visual IAS grading (3DA/3D-DSA:nlow-grade = 3, nmedium-grade = 5, nhigh-grade = 2) revealed identical results for 3DA and 3D-DSA, respectively. Quantitative IAS assessment showed a strong correlation regarding intra-/poststenotic diameters (rdintrastenotic = 0.995, pdintrastenotic = 0.0001; rdpoststenotic = 0.995, pdpoststenotic = 0.0001) and the percentual degree of luminal restriction (rNASCET 3DA = 0.981; pNASCET 3DA = 0.0001). Conclusions: The AI-based 3DA is a resilient algorithm for the visualization of IAS and shows comparable results to 3D-DSA. Hence, 3DA is a promising new method that allows a considerable patient-dose reduction, and its clinical implementation would be highly desirable.
CRIS-Team Scopus Importer:2023-03-10
Keywords: 3D angiography; artificial intelligence; deep learning; dose reduction; flat-detector computed tomography (FD-CT); innovative postprocessing; intracranial artery stenosis

A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease. - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
BACKGROUND: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. OBJECTIVE: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. METHODS: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. RESULTS: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. CONCLUSION: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
EVALuna2:470167

A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
Background: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. Objective: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. Methods: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. Results: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. Conclusion: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
CRIS-Team Scopus Importer:2021-10-29
Keywords: affective pictures; anhedonia; apathy; depression; hyposmia; non-motor symptoms; Parkinson's disease; Sniffin' Sticks

Association of Intraventricular Fibrinolysis With Clinical Outcomes in Intracerebral Hemorrhage: An Individual Participant Data Meta-Analysis. - Kuramatsu, Joji; Gerner, Stefan; Ziai, Wendy; Bardutzky, Juergen; Sembill, Jochen; Sprügel, Maximilian; Mrochen, Anne; Kölbl, Kathrin; Ram, Malathi; Avadhani, Radhika; Falcone, Guido J.; Selim, Magdy H.; et al. (Stroke, 2022)
BACKGROUND: In patients with intracerebral hemorrhage (ICH), the presence of intraventricular hemorrhage constitutes a promising therapeutic target. Intraventricular fibrinolysis (IVF) reduces mortality, yet impact on functional disability remains unclear. Thus, we aimed to determine the influence of IVF on functional outcomes. METHODS: This individual participant data meta-analysis pooled 1501 patients from 2 randomized trials and 7 observational studies enrolled during 2004 to 2015. We compared IVF versus standard of care (including placebo) in patients treated with external ventricular drainage due to acute hydrocephalus caused by ICH with intraventricular hemorrhage. The primary outcome was functional disability evaluated by the modified Rankin Scale (mRS; range: 0-6, lower scores indicating less disability) at 6 months, dichotomized into mRS score: 0 to 3 versus mRS: 4 to 6. Secondary outcomes included ordinal-shift analysis, all-cause mortality, and intracranial adverse events. Confounding and bias were adjusted by random effects and doubly robust models to calculate odds ratios and absolute treatment effects (ATE). RESULTS: Comparing treatment of 596 with IVF to 905 with standard of care resulted in an ATE to achieve the primary outcome of 9.3% (95% CI, 4.4-14.1). IVF treatment showed a significant shift towards improved outcome across the entire range of mRS estimates, common odds ratio, 1.75 (95% CI, 1.39-2.17), reduced mortality, odds ratio, 0.47 (95% CI, 0.35-0.64), without increased adverse events, absolute difference, 1.0% (95% CI, -2.7 to 4.8). Exploratory analyses provided that early IVF treatment (≤48 hours) after symptom onset was associated with an ATE, 15.2% (95% CI, 8.6-21.8) to achieve the primary outcome. CONCLUSIONS: As compared to standard of care, the administration of IVF in patients with acute hydrocephalus caused by intracerebral and intraventricular hemorrhage was significantly associated with improved functional outcome at 6 months. The treatment effect was linked to an early time window <48 hours, specifying a target population for future trials.
EVALuna2:505459

Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage. - Kölbl, Kathrin; Hock, Stefan; Xu, Mingming; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias Martin; Kallmünzer, Bernd; Kuramatsu, Joji (Frontiers in Neurology, 2024)
OBJECTIVE: Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia and thalamus) ICH who represent an important subgroup of patients at the highest risk for functional deterioration with HE due to the eloquence of the affected brain region. METHODS: From our prospective institutional database, all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 h. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modeling. RESULTS: In 322 patients with deep ICH, NCCT markers were distributed as follows: irregular shape: 69.6%, heterogenous density: 55.9%, hypodensities: 52.5%, island sign: 19.3%, black hole sign: 11.5%, and blend sign: 4.7%. Upon multivariable regression analyses, independent associations were documented with the functional outcome for irregular shape (aOR: 2.73, 95%CI: 1.42-5.22, p = 0.002), heterogenous density (aOR: 2.62, 95%CI: 1.40-4.90, p = 0.003) and island sign (aOR: 2.54, 95%CI: 1.05-6.14, p = 0.038), and with HE for heterogenous density (aOR: 5.01, 95%CI: 1.93-13.05, p = 0.001) and hypodensities (aOR: 3.75, 95%CI: 1.63-8.62, p = 0.002). CONCLUSION: NCCT markers are frequent in deep ICH patients and provide important clinical implications. Specifically, markers defined by diverging intra-hematomal densities provided associations with a 5-times higher risk for HE and a 2.5-times higher likelihood for unfavorable functional long-term outcome. Hence, these markers allow the identification of patients with deep ICH at high risk for clinical deterioration due to HE.
EVALuna2:552372

Beyond Functional Impairment: Redefining Favorable Outcome in Patients with Subarachnoid Hemorrhage - Custal, Christina; Koehn, Julia; Borutta, Matthias; Mrochen, Anne; Brandner, Sebastian; Eyupoglu, Ilker Y.; Lücking, Hannes; Hölter, Philip; Kuramatsu, Joji; Kornhuber, Johannes; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2021)
Background: For outcome assessment in patients surviving subarachnoid hemorrhage (SAH), the modified Rankin scale (mRS) represents the mostly established outcome tool, whereas other dimensions of outcome such as mood disorders and impairments in social life remain unattended so far. Objective: The aim of our study was to correlate 12-month functional and subjective health outcomes in SAH survivors. Methods: All SAH patients treated over a 5-year period received outcome assessment at 12 months, including functional scores (mRS and Barthel Index [BI]), subjective health measurement (EQ-5D), and whether they returned to work. Analyses - including utility-weighted mRS - were conducted to detect associations and correlations among different outcome measures, especially in patients achieving good functional outcome (i.e., mRS 0-2) at 12 months. Results: Of 351 SAH survivors, 287 (81.2%) achieved favorable functional outcome at 12 months. Contrary to the BI, the EQ-5D visual analog scale (VAS) showed a strong association with different mRS grades, accentuated in patients with favorable functional outcome. Despite favorable functional outcome, patients reported a high rate of impairments in activities (24.0%), pain (33.4%), and anxiety/depression (42.5%). Further, multivariable analysis revealed (i) impairments in activities (odds ratio [OR] [95% confidence interval CI]: 0.872 [0.817-0.930]), (ii) presence of depression or anxiety (OR [95% CI]: 0.836 [0.760-0.920]), and (iii) return to work (OR [95% CI]: 1.102 [0.1.013-1.198]) to be independently associated with self-reported subjective health. Conclusion: Established stroke scores mainly focusing on functional outcomes do poorly reflect the high rate of subjective impairments reported in SAH survivors, specifically in those achieving good functional outcome. Further studies are needed to investigate whether psychoeducational approaches aiming at improving coping mechanisms and perceived self-efficacy may result in higher subjective health in these patients.
CRIS-Team WoS Importer:2021-08-06

Blood Pressure and Anticoagulation Reversal Management during Off-Hours in Oral Anticoagulation-Associated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Cerebrovascular Diseases, 2020)
Background: Prevention of hematoma enlargement in oral anticoagulation-associated intracerebral hemorrhage (OAC-ICH) focuses on blood pressure (BP) reduction and OAC reversal. We investigated whether treatment efficiency and clinical outcomes differ between OAC-ICH patients admitted outside versus during regular working hours. Methods: Based on pooled data of multicenter cohort studies, we grouped OAC-ICH patients (vitamin K antagonist [VKA], non-vitamin K oral anticoagulant [NOAC]) according to on-vs. off-hour admission. Primary outcome was the functional outcome using the modified Rankin scale (mRS) dichotomized into favorable (mRS 0-3) and unfavorable (mRS 4-6) and mortality at 3 months. Secondary outcome measures included the occurrence of hematoma enlargement, the proportions of patients with systolic BP <140 mm Hg and with anticoagulation treatment achieving international normalized ratio (INR) levels <1.3 at 4 h. Propensity score matching (PSM) was performed to account for imbalances in baseline characteristics. Results: The study population consisted of 76/126 NOAC-ICH patients and 1,005/1,470 VKA patients presenting during off-hours. Functional outcome and mortality rates were not significantly different among PSM patients with VKA-ICH and NOAC-ICH during on-vs. off-hours (mRS 4-6 VKA-ICH: On-hour: 239/357 [66.9%] vs. 253/363 [69.7%] off-hour; p = 0.43; NOAC-ICH: On-hour 26/42 [61.9%] vs. off-hour: 37/57 [64.9%]; p = 0.76; mRS 6 VKA-ICH: On-hour: 127/357 [35.6%] vs. off-hour: 148/363 [40.8%]; p = 0.15;-NOAC-ICH: On-hour 17/42 [40.5%] vs. off-hour: 16/57 [28.1%]; p = 0.20). There were no differences detectable regarding the secondary outcome measures (i.e., hematoma enlargement, the proportion of patients who achieved systolic BP levels <140 mm Hg at 4 h as well as anticoagulation treatment achieving INR levels <1.3 at 4 h) in OAC patients. Conclusion: Our study implies that BP reduction and anticoagulation reversal management are well established and associated with similar rates of hematoma enlargement and clinical outcomes in on-vs. off-hour admitted OAC-ICH patients.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Clinical outcome; Intracerebral hemorrhage; Non-vitamin K oral anticoagulant; Off-hour; Oral anticoagulation; Vitamin K antagonist

Cerebral lesions in the central pain matrix are associated with headache in multiple sclerosis - Fröhlich, Kilian; Macha, Kosmas; Siedler, Gabriela; Sekita, Alexander; Haupenthal, David; Mrochen, Anne; Wang, Ruihao; Schembs, Leah; Dörfler, Arnd; Seifert, Frank; Schwab, Stefan; Winder, Klemens (Scientific Reports, 2025)
Headache is very frequent in multiple sclerosis. However, the question whether headache is just coincidental or may be secondary due to inflammatory cerebral multiple sclerosis lesions is yet to be clarified. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in patients with multiple sclerosis and comorbid headache using voxel-based lesion symptom mapping (VLSM). Patients with multiple sclerosis and headache were prospectively identified and included in a university neurological center between 2017 and 2023. Only patients with headache onset after first manifestation of multiple sclerosis were included. Demographic and clinical data were assessed, and lesion volumes calculated. Cerebral lesion sites were correlated voxel-wise with presence and absence of headache using non-parametric permutation testing. A cohort of multiple sclerosis patients served as controls for the VLSM-analysis. 48 multiple sclerosis patients with headache were included, as well as 92 controls without headache. Of the 48 patients with headache, 39 (81%) were female and nine (19%) were male. Mean age was significantly higher in headache patients than in controls (51 + / − 11 vs. 42 + / − 11 years, p < 0.05). EDSS, disease duration and lesion volumes did not significantly differ between both groups. Lesion overlap of all patients demonstrated a distribution of white matter lesions consistently in all subcortical brain areas. The VLSM-analysis showed associations between headache and lesion clusters in the left insula, left hippocampus and right thalamus. In our study, multiple sclerosis lesions in the left insula, left hippocampus and right thalamus were associated with headache in multiple sclerosis patients. The data therefore indicates that headache in multiple sclerosis may, in a proportion of patients, result from lesions in the central nervous systems’ pain processing network. Trial registration: No. 93_17 B, Ethics committee of the University Hospital Erlangen-Nürnberg.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cerebral lesions; Headache; Multiple sclerosis; Voxel-based lesion symptom mapping

Cerebral lesions sites in neurosarcoidosis: a lesion mapping study - Fröhlich, Kilian; Mrochen, Anne; Wang, Ruihao; Haupenthal, David; Macha, Kosmas; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Schwab, Stefan; Winder, Klemens (Journal of Neurology, 2023)
Background and purpose: Sarcoidosis is a granulomatous disease of unknown etiology affecting the central nervous system in up to 15% of the patients. Diagnosis of neurosarcoidosis is very challenging due to the heterogeneity of its clinical manifestation. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in neurosarcoidosis patients using voxel-based lesion symptom mapping (VLSM). Methods: Patients with neurosarcoidosis were retrospectively identified and included between 2011 and 2022. Cerebral lesion sites were correlated voxel-wise with presence and absence of neurosarcoidosis using non-parametric permutation test. Multiple sclerosis patients served as controls for the VLSM-analysis. Results: Thirty-four patients (mean age 52 ± 15 years) of whom 13 were diagnosed with possible, 19 with probable and 2 with confirmed neurosarcoidosis were identified. Lesion overlap of neurosarcoidosis patients demonstrated a distribution of white matter lesions in all brain areas, with a periventricular predilection similar to multiple sclerosis. In contrast to multiple sclerosis controls, no propensity for lesions in proximity of the corpus callosum was observed. Neurosarcoidosis lesions appeared smaller and lesion volume was lower in the neurosarcoidosis cohort. The VLSM analysis showed minor associations between neurosarcoidosis and damaged voxels in the bilateral frontobasal cortex. Conclusions: The VLSM analysis yielded significant associations in the bilateral frontal cortex, suggesting that leptomeningeal inflammatory disease with following cortical involvement is a quite specific feature in neurosarcoidosis. Lesion load was lower in neurosarcoidosis than in multiple sclerosis. However, no specific pattern of subcortical white matter lesions in neurosarcoidosis was revealed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cerebral lesions; Neurosarcoidosis; Sarcoidosis; Voxel-based lesion symptom mapping

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Changes in Gastrointestinal Microbiome Composition in PD: A Pivotal Role of Covariates - Cosma-Grigorov, Alexandra; Meixner, Holger; Mrochen, Anne; Wirtz, Stefan; Winkler, Jürgen; Marxreiter, Franz (Frontiers in Neurology, 2020)
Altered gut microbiota may trigger or accelerate alpha-synuclein aggregation in the enteric nervous system in Parkinson's disease (PD). While several previous studies observed gut microbiota alterations in PD, findings like diversity indices, and altered bacterial taxa itself show a considerable heterogeneity across studies. We recruited 179 participants, of whom 101 fulfilled stringent inclusion criteria. Subsequently, the composition of the gut microbiota in 71 PD patients and 30 healthy controls was analyzed, sequencing V3–V4 regions of the bacterial 16S ribosomal RNA gene in fecal samples. Our goal was (1) to evaluate whether gut microbiota are altered in a southern German PD cohort, (2) to delineate the influence of disease duration, stage, and motor impairment, and (3) to investigate the influence of PD associated covariates like constipation and coffee consumption. Aiming to control for a large variety of covariates, strict inclusion criteria were applied. Finally, propensity score matching was performed to correct for, and to delineate the effect of remaining covariates (non-motor symptom (NMS) burden, constipation, and coffee consumption) on microbiota composition. Prior to matching altered abundances of distinct bacterial classes, orders, families, and genera were observed. Both, disease duration, and stage influenced microbiome composition. Interestingly, levodopa equivalent dose influenced the correlation of taxa with disease duration, while motor impairment did not. Applying different statistical tests, and after propensity score matching to control for NMS burden, constipation and coffee consumption, Faecalibacterium and Ruminococcus were most consistently reduced in PD compared to controls. Taken together, similar to previous studies, alterations of several taxa were observed in PD. Yet, further controlling for PD associated covariates such as constipation and coffee consumption revealed a pivotal role of these covariates. Our data highlight the impact of these PD associated covariates on microbiota composition in PD. This suggests that altered microbiota may mediate the protective effect of i.e., coffee consumption and the negative effect of constipation in PD.
CRIS-Team Scopus Importer:2020-10-16
Keywords: biomarker; constipation; covariates; gut; microbiome; non-motor symptoms; Parkinson's disease

Disability-Adjusted Life-Years Associated with Intracerebral Hemorrhage and Secondary Injury - Haupenthal, David; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (JAMA Network Open, 2021)
Importance: Intracerebral hemorrhage (ICH) contributes significantly to the global burden of disease. Objective: To examine the association of ICH and secondary injury with disability-adjusted life-years (DALYs) for the individual patient. Design, Setting, and Participants: This cohort study was conducted using data from the Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage study. Consecutive patients admitted to a single tertiary care center from January 1, 2006, to December 31, 2015, were included. The sample comprised patients with oral anticoagulation-associated ICH (OAC-ICH) or primary spontaneous ICH (non-OAC-ICH). Statistical analysis was conducted from October 1 to December 31, 2020. Exposures: ICH occurrence and secondary injury. Main Outcomes and Measures: DALYs, years of life lost (YLL), and years lived with disability (YLD) were analyzed by hematoma location, ICH volume, and secondary injury (ie, hematoma expansion [HE], intraventricular hemorrhage [IVH], and perihemorrhagic edema [PHE]). Results: Among 1322 patients with ICH, 615 (46.5%) were women and the mean (SD) age at hospital admission was 71 (13) years; ICH was associated with a mean (SD) of 9.46 (8.08) DALYs, 5.72 (8.29) YLL, and 3.74 (5.95) YLD. There were statistically significant differences in mean (SD) DALYs by extent of hematoma volume (< 10 mL ICH: 7.05 [6.79] DALYs; 10-30 mL ICH: 9.91 [8.35] DALYs; >30 mL ICH: 12.42 [8.47] DALYs; P <.001) and ICH location (deep location: 10.60 [8.35] DALYs; lobar location: 8.18 [7.63] DALYs; cerebellum: 8.14 [6.80] DALYs; brainstem: 12.63 [9.21] DALYs; P <.001). Regarding population-level disease burden of secondary injuries after ICH, there was a statistically significant difference in mean (SD) by injury type, with 0.94 (3.19) DALYs for HE, 2.45 (4.16) DALYs for IVH, and 1.96 (2.66) DALYs for PHE (P <.001) among the entire ICH cohort. Regarding individual-level exposure to secondary injuries after ICH, there were a mean (SD) 7.14 (6.62) DALYs for HE, 4.58 (4.75) DALYs for IVH, and 3.35 (3.28) DALYs for PHE among patients with ICH affected by secondary injuries. Conclusions and Relevance: These findings suggest that there is a high burden of disability associated with ICH and secondary injuries, and the findings may guide public health strategies. The study findings further suggest that IVH and PHE may be relevant for the overall outcome of patients with ICH, that DALYs may represent a viable outcome parameter for studies to evaluate treatment outcomes in ICH research, and that IVH and PHE may represent potential treatment targets..
CRIS-Team Scopus Importer:2021-07-30

EARLY MANIFESTATION AND RAPID SYMPTOM PROGRESSION IN A CASE OF HOMOZYGOUS TRINUCLEOTIDE EXPANSION IN THE TBP-GENE IN AUTOSOMAL DOMINANT SPINOCEREBELLAR ATAXIA TYPE 17 - Forras, Patricia Vanda; Wilfling, Sibylle; Mrochen, Anne; Dufke, Claudia; Linker, Ralf; Hehr, Ute; Kohl, Zacharias (JOURNAL OF NEUROLOGY NEUROSURGERY AND PSYCHIATRY, 2022)
CRIS-Team WoS Importer:2022-12-23

Incidence, temporal profile and neuroanatomic correlates of poststroke epilepsy - Winder, Klemens; Bobinger, Tobias; Seifert, Frank; Mrochen, Anne; Haupenthal, David; Knott, Michael; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Fröhlich, Kilian (Journal of Neuroimaging, 2023)
Background and Purpose: The relationship between ischemic stroke site and occurrence of poststroke epilepsy (PSE) is incompletely understood. This study intended to evaluate incidence and temporal profiles of seizures and to correlate ischemic lesion sites with PSE using voxel-based lesion symptom mapping (VLSM). Methods: Patients with imaging-confirmed first-ever ischemic stroke without prior history of epilepsy were prospectively included. Demographic data, cardiovascular risk factors, and National Institute of Health Stroke Scale (NIHSS) scores were assessed. Data on seizures and modified Rankin scale scores were determined within a 90-day period after stroke onset. Ischemic lesion sites were correlated voxel wise with occurrence of PSE using nonparametric permutation test. Age- and sex-matched patients with first-ever ischemic strokes without PSE after 90 days served as controls for the VLSM analysis. Results: The stroke database contained 809 patients (mean age: 68.4 ± 14.2 years) with first-ever imaging-confirmed ischemic strokes without history of epilep. Incidence of PSE after 90-day follow-up was 2.8%. Five additional patients were admitted to the emergency department with a seizure after 90-day follow-up. Fifty percent of the seizures occurred in the acute phase after stroke. PSE patients had higher NIHSS scores and infarct volumes compared to controls without PSE (p <.05). PSE patients had infarcts predominantly involving the cerebral cortex. The hemisphere-specific VLSM analysis shows associations between PSE and damaged voxels in the left-hemispheric temporo-occipital transition zone. Conclusions: The data indicate that PSE occurs in a small proportion of patients with rather large ischemic strokes predominantly involving the cerebral cortex. Especially patients with ischemic lesions in the temporo-occipital cortex are vulnerable to develop PSE.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ischemic stroke; poststroke epilepsy; voxel-based lesion symptom mapping

Individual participant data analysis comparing acute stroke patients with anterior versus posterior circulation dissections - Zhang, Yanan; Zhang, Yang; Fröhlich, Kilian; Mrochen, Anne; Mühlen, Iris; Lang, Stefan; Lehmann, Sophie; Gerner, Stefan T.; Huttner, Hagen B.; Schwab, Stefan; He, Li; Bobinger, Tobias (Clinical Neurology and Neurosurgery, 2024)
Background: Cervical artery dissection (CAD) is a relevant etiology of transient ischemic attacks and strokes. Several trials explored the significance of specific antithrombotic treatments, i.e. oral anticoagulation (OAC) versus antiplatelet treatment (APT), on recurrent ischemic complications and clinical outcomes. As overall incidence rates of complications were low there is still controversy which antithrombotic treatment should be used. However, up to now there has been no systematic investigation among CAD-patients with ischemic stroke specifically comparing clinical course and outcome of patients with anterior versus posterior CAD. Methods: We performed an individual participant data analysis of patients with CAD and ischemic stroke. Over a five-year period we pooled data from three sites (i.e. West China Hospital, Chengdu, China as well as Erlangen and Giessen University Hospitals, Germany) and enrolled patients with CAD-associated ischemic stroke. Patient demographics, clinical and in-hospital measures as well as radiological data were retrieved from institutional databases. Clinical follow-up was over 6 months and included data on recurrent ischemic strokes and hemorrhages as well as clinical functional outcome assessed by the modified Rankin Scale dichotomized into favourable (mRS=0–2) and unfavourable. Results: A total of 203 patients with CAD were included of which n=112 had anterior and n=91 had posterior CAD. Patients with posterior CAD were younger (46.0 vs. 41.0 y; p<0.001) than patients with anterior CAD and showed less often arterial hypertension. (42.0 % vs. 28.6 %; p<0.048). Antithrombotic treatment with APT and OAC was similarily distributed among patients with anterior and posterior CAD and not significantly differently related to ischemic or hemorrhagic complications during follow-up (all p=n.s.). Main difference between Chinese and German patients were mode of antithrombotic treatment consisting predominantly of APT in China compared to OAC in Germany. Functional outcome overall was good, yet worse in patients with anterior CAD compared to posterior CAD (80.2 % favorable in anterior CAD vs. 92.2 % in posterior CAD (p=0.014). Conclusion: This study provides evidence that anterior and posterior CAD show baseline imbalances regarding age and comorbidity which may affect clinical outcome. There are no signals of superiority or harm of any specific mode of antithrombotic treatment nor relevant discrepancies in clinical outcome among Chinese and German CAD-associated stroke patients.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Acute ischemic stroke; Antiplatelet treatment; Cervical artery dissections; Clinical outcome; Oral anticoagulation

Influence of bundled care treatment on functional outcome in patients with intracerebral hemorrhage - Mrochen, Anne; Song, Yu; Harders, Verena; Sembill, Jochen; Sprügel, Maximilian; Hock, Stefan; Lang, Stefan; Engelhorn, Tobias; Kallmünzer, Bernd; Volbers, Bastian; Kuramatsu, Joji (Frontiers in Neurology, 2024)
Background and aims: General guideline recommendations in patients with intracerebral hemorrhage (ICH) include blood pressure-, temperature- and glucose management. The therapeutic effect of such a “care bundle” (blood pressure lowering, glycemic control, and treatment of pyrexia) on clinical outcomes becomes increasingly established. For the present study, we aimed to investigate associations of strict bundled care treatment (BCT) with clinical outcomes and characterize associations with key outcome effectors such as hematoma enlargement (HE) and peak perihemorrhagic edema (PHE). Methods: We screened consecutive ICH patients (n = 1,322) from the prospective UKER-ICH cohort study. BCT was defined as achieving and maintaining therapeutic ranges for systolic blood pressure (110–160 mmHg), glucose (80–180 mg/dL), and body temperature (35.5–37.5°C) over the first 72 h. The primary outcome was the functional outcome at 12 months (modified Rankin Scale (mRS) 0–3). Secondary outcomes included mortality at 12 months, the occurrence of hematoma enlargement, and the development of peak perihemorrhagic edema. Confounding was addressed by a doubly robust methodology to calculate the absolute treatment effect (ATE) and by calculating e-values. Results: A total of 681 patients remained for analysis, and 182 patients fulfilled all three BCT criteria and were compared to 499 controls. The ATE of BCT to achieve the primary outcome was 9.3%, 95% CI (1.7 to 16.9), p < 0.001; e-value: 3.1, CI (1.8). Mortality at 12 months was significantly reduced by BCT [ATE: −12.8%, 95% CI (−19.8 to −5.7), p < 0.001; e-value: 3.8, CI (2.2)], and no association was observed for HE or peak PHE. Significant drivers of BCT effect on the primary outcome were systolic blood pressure control (ATE: 15.9%) and maintenance of normothermia (ATE: 10.9%). Conclusion: Strict adherence to this “care bundle” over the first 72 h during acute hospital care in patients with ICH was independently associated with improved functional long-term outcome, driven by systolic blood pressure control and maintenance of normothermia. Our findings strongly warrant prospective validation to determine the generalizability especially in Western countries. Clinical trial registration:ClinicalTrials.gov, identifier [ID: NCT03183167].
CRIS-Team Scopus Importer:2024-08-30
Keywords: bundle; HE; ICH; PHE; treatment

Invasiveness and Clinical Outcomes of Off-Hour Admissions in Patients with Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Kuramatsu, Joji; Lücking, Hannes; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2019)
BACKGROUND: Whether time of hospital admission-during or outside regular working hours-affects functional outcome in intracerebral hemorrhage (ICH) is unestablished as previous analyses have focused on mortality only. We here investigate whether on- versus off-hour hospital admission in ICH is associated with levels of invasiveness and clinical outcomes. METHODS: Based on the UKER registry (NCT03183167) we grouped ICH-patients according to on- versus off-hour hospital admission. Primary outcome measures was functional outcome after 3 months using the modified Rankin scale (mRS) dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6). Multivariate regression analyses were used to adjust for baseline imbalances, and subgroup analyses were performed to explore associations of on- versus off-hour admission with invasiveness of therapeutic interventions. RESULTS: A total of 438/1269 (34.5%) of ICH-patients were admitted during regular working hours. Mortality rates were not significantly different among patients with on- versus off-hour admission. On-hour patients showed a significantly larger proportion of patients with favorable outcome (on-hour: mRS = 0-3 after 3 months: 176/416 (42.3%) versus off-hour: 265/784 (33.8%); P = .004). Analysis of invasive therapeutic interventions revealed that likelihood of favorable outcome was significantly increased among on-hour admitted patients who did not require neurosurgical interventions (no external ventricular drain n = 349, OR: 1.67[1.13-2.48], P < .05; no hematoma evacuation surgery n = 423, OR: 1.51[1.07-2.14], P < .05). CONCLUSION: This study verified an "off-hour effect" in ICH that relates to functional outcome, rather than mortality, and which may be linked to different levels of invasive therapeutic interventions in patients admitted during off-hour.
EVALuna2:206735

Long-Term Survival, Burden of Disease, and Patient-Centered Outcomes in Maximally Treated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Sekita, Alexander; Balk, Stefanie; Haupenthal, David; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Macha, Kosmas; Schwab, Stefan; Kuramatsu, Joji; Sembill, Jochen (Annals of Clinical and Translational Neurology, 2025)
Objective: Increasing evidence shows that patients with intracerebral hemorrhage (ICH) can achieve better-than-expected outcomes with aggressive therapy. However, real-world long-term data, patient-centered outcomes, and societal measures after maximal ICH treatment are lacking. This study aimed to analyze 5-year survival, utility-weighted functional outcomes, and burden of disease in maximally treated ICH patients, stratified by max-ICH Score. Methods: This study investigated consecutive patients with spontaneous ICH included in the single-center Longitudinal Cohort Study on ICH Care (UKER-ICH, NCT03183167, 2006–2015). We included all patients without early care limitations, hereinafter referred to as maximally treated. We analyzed the stratification by max-ICH Score of cumulative 5-year survival using Kaplan–Meier estimates and COX regression modeling, disease burden using disability-adjusted life years (DALYs), and patient-centered outcome at 12 months using the Utility-Weighted modified Rankin Scale (UW-mRS). Results: The 5-year survival rate of the included 1022 maximally treated patients was 53%, stratified by max-ICH Score (0 points: 85%, 1: 91%, 2: 69%, 3: 59%, 4: 47%, 5: 32%, 6: 29%, 7: 18%, ≥ 8: 0%, log-rank p < 0.001). The mean number of DALYs was 8.94 (±8.15, standard deviation [SD]), consisting of 4.27 years of life lost (±7.79, SD) and 4.67 years lived with disability (±6.38, SD). Patients with a max-ICH Score of 5 had the highest burden of disease (12.76 [±9.43, SD]). The mean UW-mRS at 12 months was 0.45 (±0.37, SD) and decreased with increasing max-ICH Score (0: 0.80 [±0.23], 1: 0.73 [±0.29], 2: 0.67 [±0.29], 3: 0.50 [±0.34], 4: 0.39 [±0.34], 5: 0.25 [±0.30], 6: 0.19 [±0.28], 7: 0.16 [±0.26], ≥ 8: 0.08 [±0.22], p < 0.001). Interpretation: These observational data, stratified by max-ICH Score, provide patients and treating physicians with an initial severity assessment in terms of potential long-term patient-centered outcomes and burden of disease following maximal treatment.
CRIS-Team Scopus Importer:2025-04-25
Keywords: intracerebral hemorrhage prognosis; patient-centered outcomes; stroke disability burden

Multisensory deficit of hedonic perception in Parkinson's Disease - Martini, Max; Utz, Katrin; Mrochen, Anne; Klucken, Jochen; Renner, Bertold; Winkler, Jürgen; Marxreiter, Franz (2019)
EVALuna2:213355

Neutrophil-to-lymphocyte ratio is associated with increased cerebral blood flow velocity in acute bacterial meningitis - Giede-Jeppe, Antje; Atay, Selim; Koehn, Julia; Mrochen, Anne; Lücking, Hannes; Hölter, Philip; Volbers, Bastian; Huttner, Hagen B.; Hueske, Lena; Bobinger, Tobias (Scientific Reports, 2021)
In community-acquired bacterial meningitis (CABM) intracranial vascular alterations are devastating complications which are triggered by neuroinflammation and result in worse clinical outcome. The Neutrophil-to-Lymphocyte ratio (NLR) represents a reliable parameter of the inflammatory response. In this study we analyzed the association between NLR and elevated cerebral blood flow velocity (CBFv) in CABM-patients. This study included all (CABM)-patients admitted to a German tertiary center between 2006 and 2016. Patients’ demographics, in-hospital measures, neuroradiological data and clinical outcome were retrieved from institutional databases. CBFv was assessed by transcranial doppler (TCD). Patients’, radiological and laboratory characteristics were compared between patients with/without elevated CBFv. Multivariate-analysis investigated parameters independently associated with elevated CBFv. Receiver operating characteristic(ROC-)curve analysis was undertaken to identify the best cut-off for NLR to discriminate between increased CBFv. 108 patients with CABM were identified. 27.8% (30/108) showed elevated CBFv. Patients with elevated CBFv and normal CBFv, respectively had a worse clinical status on admission (Glasgow Coma Scale: 12 [9–14] vs. 14 [11–15]; p = 0.005) and required more often intensive care (30/30 [100.0%] vs. 63/78 [80.8%]; p = 0.01).The causative pathogen was S. pneumoniae in 70%. Patients with elevated CBFv developed more often cerebrovascular complications with delayed cerebral ischemia (DCI) within hospital stay (p = 0.031). A significantly higher admission-NLR was observed in patients with elevated CBFv (median [IQR]: elevated CBFv:24.0 [20.4–30.2] vs. normal CBFv:13.5 [8.4–19.5]; p < 0.001). Multivariate analysis, revealed NLR to be significantly associated with increased CBFv (Odds ratio [95%CI] 1.042 [1.003–1.084]; p = 0.036). ROC-analysis identified a NLR of 20.9 as best cut-off value to discriminate between elevated CBFv (AUC = 0.713, p < 0.0001, Youden's Index = 0.441;elevated CBFv: NLR ≥ 20.9 19/30[63.5%] vs. normal CBFv: NLR > 20.9 15/78[19.2%]; p < 0.001). Intracranial vascular complications are common among CABM-patients and are a risk factor for unfavorable outcome at discharge. Elevated NLR is independently associated with high CBFv and may be useful in predicting patients’ prognosis.
CRIS-Team Scopus Importer:2021-06-18

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy - Sembill, Jochen; Knott, Michael; Xu, Mingming; Röder, Sebastian; Hagen, Manuel; Sprügel, Maximilian; Mrochen, Anne; Borutta, Matthias; Hölter, Philip; Engelhorn, Tobias Martin; Rothhammer, Veit; Macha, Kosmas; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: In patients with lobar intracerebral hemorrhage (ICH), etiologic characterization represents a tradeoff between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy (CAA). METHODS: This external validation analyzed 210 consecutive patients with lobar ICH and available CT and MRI studies from a prospective single-center observational cohort study (2006-2015, Longitudinal Cohort Study on ICH Care [UKER-ICH,] NCT03183167). We investigated the interrater variability and diagnostic accuracy of the simplified Edinburgh CT-based criteria for identification of ICH associated with probable CAA according to MRI-based modified Boston criteria as a reference standard. We evaluated the utility of the simplified Edinburgh criteria by decision curve analysis, comparing the theoretical clinical net benefit (weighted benefit-harm at varying threshold probabilities) of the high-risk category (finger-like projections and subarachnoid hemorrhage) for ruling in and the low-risk category (neither finger-like projections nor subarachnoid hemorrhage) for ruling out with the assumptions of no or all patients having CAA (default strategies). RESULTS: Of 210 patients, 70 (33.3%) had high risk, 67 (31.9%) had medium risk, and 73 (34.8%) had low risk for CAA-associated ICH according to simplified Edinburgh CT criteria, showing moderate interrater variability. Discrimination was good (area under the receiver operating characteristics curve 0.74, 95% CI 0.67-0.81) without evidence of poor calibration (Hosmer-Lemeshow, p = 0.54) for validation of MRI-based diagnosis of probable CAA (n = 94 of 210, 44.8%). The rule-in criteria (high risk), had 87.1% (79.3%-92.3%) specificity, and the rule-out criteria (low risk), had 80.9% (71.1%-88.0%) sensitivity. Decision curve analysis suggested a theoretical clinical net benefit for ruling in but not for ruling out probable CAA compared to default strategies. DISCUSSION: Applying the simplified Edinburgh CT criteria during diagnostic workup seems clinically useful and may accurately identify CAA in patients with lobar ICH. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT03183167. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with lobar hemorrhages, the simplified Edinburgh criteria accurately identify those at high risk of CAA.
CRIS-Team Scopus Importer:2022-06-03

The influence of liver dysfunction (LD) on functional outcome in intracerebral hemorrhage - Beuscher, Vanessa; Sprügel, Maximilian; Mrochen, Anne; Hölter, Philip; Lang, Stefan; Kuramatsu, Joji; Huttner, Hagen (Journal für Anasthesie und Intensivbehandlung, 2021)
CRIS-Team Scopus Importer:2024-12-16

Thrombocytopenia and Clinical Outcomes in Intracerebral Hemorrhage: A Retrospective Multicenter Cohort Study - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2021)
BACKGROUND AND PURPOSE: The impact of platelets on hematoma enlargement (HE) of intracerebral hemorrhage (ICH) is not yet sufficiently elucidated. Especially the role of reduced platelet counts on HE and clinical outcomes is still poorly understood. This study investigated the influence of thrombocytopenia on HE, functional outcome, and mortality in patients with ICH with or without prior antiplatelet therapy (APT). METHODS: Individual participant data of multicenter cohort studies (multicenter RETRACE program [German-Wide Multicenter Analysis of Oral Anticoagulation-Associated Intracerebral Hemorrhage] and single-center UKER-ICH registry [Universitätsklinikum Erlangen Cohort of Patients With Spontaneous ICH]) were grouped into APT and non-APT ICH patients according to the platelet count, that is, with or without thrombocytopenia (cells <150×109/L). Of all patients, 51.5% (1124 of 2183) were on vitamin K antagonist. Imbalances in baseline characteristics including proportions of vitamin K antagonist patients were addressed using propensity score matching. Outcome analyses included HE (>33%), as well as mortality and functional outcome, after 3 months using the modified Rankin Scale, dichotomized into favorable (modified Rankin Scale score, 0-3) and unfavorable (modified Rankin Scale score, 4-6). RESULTS: Of overall 2252 ICH patients, 11.4% (52 of 458) under APT and 14.0% (242 of 1725) without APT presented with thrombocytopenia on admission. The proportion of patients with HE was not significantly different between patients with or without thrombocytopenia among APT and non-APT ICH patients after propensity score matching (HE: APT patients: 9 of 40 [22.5%] thrombocytopenia versus 27 of 115 [23.5%] nonthrombocytopenia, P=0.89; non-APT patients: 54 of 174 [31.0%] thrombocytopenia versus 106 of 356 [29.8%] nonthrombocytopenia, P=0.77). In both (APT and non-APT) propensity score matching cohorts, there were no significant differences regarding functional outcome. Mortality after 3 months did not differ among non-APT patients, whereas the mortality rate was significantly higher for APT patients with thrombocytopenia versus APT patients with normal platelet count (APT: 29 of 46 [63.0%] thrombocytopenia versus 58 of 140 [41.4%] nonthrombocytopenia, P=0.01; non-APT: 95 of 227 [41.9%] thrombocytopenia versus 178 of 455 [39.1%] nonthrombocytopenia, P=0.49). CONCLUSIONS: Our study implies that thrombocytopenia does not affect rates of HE and functional outcome among ICH patients, neither in patients with nor without APT. In light of increased mortality, the significance of platelet transfusions for ICH patients with thrombocytopenia and previous APT should be explored in future studies.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cohort studies; hematoma enlargement; intracerebral hemorrhage; platelet count; thrombocytopenia

Value of initial C-reactive protein levels in status epilepticus outcome prediction - Madzar, Dominik; Reindl, Caroline; Mrochen, Anne; Hamer, Hajo; Huttner, Hagen (Epilepsia, 2021)
The role of neuroinflammation in the pathophysiology of seizures is increasingly recognized, and the evaluation of potential biochemical markers of inflammatory processes in seizures and status epilepticus (SE), such as C-reactive protein (CRP), has gained attention. The present study assessed the first CRP level obtained in an SE episode regarding its value for SE outcome prediction. Among 362 admissions for SE during the study period, 231 episodes satisfied the inclusion criteria. Higher initial CRP concentrations were independently associated with in-hospital mortality and poor functional outcome at discharge in logistic regression models adjusting for SE severity, severity of SE etiology, and development of treatment refractoriness. Therefore, initial CRP levels may add to the prediction of SE prognosis. The pathomechanisms through which CRP is linked with the prognosis of SE, however, remain to be established.
CRIS-Team Scopus Importer:2021-03-05
Keywords: acute phase proteins; C-reactive protein; inflammation; laboratory parameters; outcome; status epilepticus

"Virtual stent" - clinical evaluation and user experience of on-the-fly stent simulation in treatment of cerebral aneurysms - Lücking, Hannes; Birkhold, Annette; Hölter, Philip; Lang, Stefan; Gölitz, Philipp; Schmidt, Manuel; Mrochen, Anne; Brandner, Sebastian; Dörfler, Arnd (Interventional Neuroradiology, 2021)
Background Predicting final stent position can be challenging when treating cerebral aneurysms. Third-Party software proved helpful in selecting proper stents in treatment planning. Recent angiographic systems provide basic stent simulation capabilities integrated in the post-processing software to simulate stent position. Goal of this analysis was to evaluate the simulation process and correlation with definite stent position. Materials and Methods Thirty-three datasets with fusiform (n = 10) and saccular (n = 23) aneurysms, treated with stent or flow-diverter, were processed. A "virtual stent" of the same (nominal) size was simulated and its position was compared to the treatment result. Simulated length was rated in five grades (too short, shorter, equal, longer, too long), with regard to side-branches, anchoring zone etc. Simulation quality (centerline recognition/adherence to vessel margins) was rated in three grades (no, minor or major corrections required). Results Simulation was successful in 32/33 cases (97%), with one abortive attempt (3%). In 27/33 simulations (82%), there was no need for centerline refinement. Minor corrections were necessary in four and major corrections in two cases. Simulated nominal length was rated "equal" in 14/33 (42%) cases and "shorter" or "longer" - but within acceptable range - in each 9/33 (27%) cases. Conclusion Basic stent simulation tools available with genuine angiographic workplace software can provide good simulation capabilities without need for third-party equipment. They can facilitate treatment planning and help to avoid shortage of devices. Yet, lack of calculation of foreshortening in large vessel diameters leaves the user to rely on their experience to account for device-specific properties.
CRIS-Team WoS Importer:2021-11-12